Відповідальність як мета освіти - Чеботарьов, Микола Корнійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розкрито роль відповідальності в житті людини і функціонуванні суспільства. Показано, що вона вимагає включення розвитку відповідальності в систему цілей освіти. Розглянуто основні передумови успішного їх досягнення. Підкреслено визначальну роль педагога, його відповідальності в особистісному розвитку майбутніх фахівців.

The role of responsibility in human life and the functioning of society is revealed. It is shown that it requires the inclusion of the development of responsibility in the system of educational goals. The basic prerequisites for their successful achievement are considered. The determining role of the teacher, his responsibility in the personal development of future specialists is emphasized.
Вresponsibility as the objective of education
Keywords: природа людини; проблеми; розвиток; умови; human nature; problems; development; conditions